Functional evidence implicating NOTCH2 missense mutations in primary ovarian insufficiency etiology (2019)
Primary ovarian insufficiency (POI) is a frequently occurring disease affecting women under 40 years old. Recently, we have analyzed unrelated POI women via whole exome sequencing (WES) and identified NOTCH2 mutations underlying possible functional effects. The present study involved reanalyzing of WES assays. We used in the KGN granulosa-like cell model, a synthetic gene reporter construct driving luciferase gene expression to assess the functional effects of five NOTCH2 mutations identified in POI patients. We found that NOTCH2-p.Ser1804Leu, p.Ala2316Val, and p.Pro2359Ala mutations had a functional impact on the protein's transcriptional activity. The results have demonstrated for the first time that NOTCH2 mutations contribute to POI etiology. We therefore recommend sequencing NOTCH2's open reading frame in large panels of POI patients to establish an accurate genotype–phenotype correlation. We cannot rule out the fact that patients affected by Alagille syndrome carrying NOTCH2 mutations may suffer ovarian dysfunction. © 2018 Wiley Periodicals, Inc.